A unique case of substance abuse - K Krishnamurthy; Wilona J Braganza (Wolters Kluwer Medknow Publications, 2013)
The desire to periodically alter consciousness by using psychoactive substances is an innate drive similar to hunger, thirst or sex. WHO has defined various substances, psychoactive or otherwise which may potentially be abused. An innovative method of intake was observed while evaluating a patient under our care. An 18-year-old boy was brought for consultation with a history of multiple substance use and anti-social personality traits. On interviewing, patient reported of the use of a white powder in the form of a snake bite. Patient described the technique of the snake bite and his experience following the bite. There have been two previous reports of patients resorting to snake bites for recreational purposes and this unique and extreme mode of undergoing a psychoactive experience needs to be studied further.